Immunological properties of the human Goodpasture target antigen. - Weber, M (1988)
The globular domain NC1 of human basement membrane collagen IV was isolated from glomerular basement membrane after collagenase digestion by chromatographic purification. The human NC1 appears as a hexamer of 160 kD by molecular sieve chromatography which migrates as a single molecule at gel electrophoresis without sodium dodecyl sulphate (SDS). Reversible dissociation of the hexamer into monomers and dimers was achieved by 6 M guanidine-HC1, SDS, or at pH values less than 4.0. All the subunits of 26 kD, 28 kD, 44 kD, and 50 kD showed reactivity with anti-GBM antibodies on immunoblotting. Inhibition-ELISA demonstrated that the intact hexamer also binds to anti-GBM antibodies at higher NC1 concentrations. However, dose-response curves indicated an approximately 20-50-fold increase in reactivity after dissociation of the hexamer in 6 M guanidine-HC1. Analysis of thermostability demonstrated that heating for 24 h at 37 degrees C or 56 degrees C did not alter the reactivity to anti-GBM antibodies, while reactivity was lost after heating for more than 120 min at 95 degrees C. In contrast to bovine NC1 unfolding of the antigen occurs immediately and does not require elevated temperature. Rotary shadowing of human NC1 at neutral pH revealed homogeneous globules. Distinct but incomplete dissociation into monomers and dimers could be observed at pH 2.5. These in vitro data of the human NC1 domain give further evidence that most of the Goodpasture epitopes are sequestered within the NC1 hexamer and support the hypothesis that production of anti-GBM autoantibodies may be initiated after dissociation of the hexamer has been induced, possibly by a toxic or infective episode.